Laser ablation – inductively couple plasma – mass spectrometry/laser induced break down spectroscopy: a tandem technique for uranium particle characterization. Issue 9 (25th April 2017) - Manard, Benjamin T.; Derrick Quarles, C.; Wylie, E. Miller; Xu, Ning
Abstract : Laser ablation – inductively coupled plasma – mass spectrometry (LA-ICP-MS) in tandem with laser induced breakdown spectroscopy (LIBS) was employed to chemically map and characterize uranium particles. Abstract : Laser ablation – inductively coupled plasma – mass spectrometry (LA-ICP-MS) in tandem with laser induced breakdown spectroscopy (LIBS) was employed to chemically map and characterize uranium particles. The uranium particles were doped in various concentrations (0.01, 0.1, 1.0, and 2.0%) to a 50 : 50 Ni : Fe mixture. There was an excellent correlation in regards to concentration and the LA-ICP-MS measurements. In addition, the isotopic composition of the uranium particles was determined within 10% measurement uncertainty. LIBS measurements also showed strong agreement in the particle mapping when compared to the LA-ICP-MS analysis. Moreover, the total analysis time for a 5 × 5 mm area was only 50 minutes. These data suggest that the tandem LA-ICP-MS/LIBS technique can provide rapid and valuable information for nuclear material safeguards and actinide material characterization.